Clearing the Brain’s Cobwebs: The Role of Autophagy in Neuroprotection - Bossy, Blaise (Bentham Science Publishers Ltd, 2008)
Protein aggregates or inclusion bodies are common hallmarks of age-related neurodegenerative disorders. Why these aggregates form remains unclear. Equally debated is whether they are toxic, protective, or simple by-products. Increasing evidence, however, supports the notion that in general aggregates confer toxicity and disturb neuronal function by hampering axonal transport, synaptic integrity, transcriptional regulation, and mitochondrial function. Thus, neuroscientists in search of effective treatments to slow neural loss during neurodegeneration have long been interested in finding new ways to clear inclusion bodies. Intriguingly, two studies using conditional neuron-specific gene ablations of autophagy regulators in mice revealed that autophagy loss elicits inclusion body formation and a neurodegenerative cascade.Such studies indicate autophagy may be a built-in defense mechanism to clear the nervous system of inclusion bodies.This new finding has implications for our understanding of aging and neurodegeneration and the development of new therapies. First, we discuss the pathways underlying autophagy and its controversial role in cell death and survival regulation.We then discuss the physiological role of autophagy in the aging process of the nervous system. In the final portion of this review, we discuss the therapeutic promise of inducing autophagy and the potential side effects of such treatments.